2015
DOI: 10.1016/j.smim.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Early hematopoiesis and macrophage development

Abstract: The paradigm that all blood cells are derived from hematopoietic stem cells (HSCs) has been challenged by two findings. First, there are tissue-resident hematopoietic cells, including subsets of macrophages that are not replenished by adult HSCs, but instead are maintained by self-renewal of fetal-derived cells. Second, during embryogenesis, there is a conserved program of HSC-independent hematopoiesis that precedes HSC function and is required for embryonic survival. The presence of waves of HSC-independent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
132
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 92 publications
3
132
0
1
Order By: Relevance
“…Here, we used C57 / Bl6 WT mice to show that CD45‐positive cells are detected in endocardial cushions of primitive aortic valves at embryonic day 14.5, and reactivity is also observed in the mitral position, but the percentage of cells is significantly lower (Figure A). It is not known whether these cells are embryonic hematopoietic stem cells derived from primitive or definitive hematopoiesis, or tissue‐resident hematopoietic cells . Similar percentages of CD45‐positive cells are observed at postnatal stages in both valve sets (≈1.2% aortic, ≈2.6% mitral), but the percent significantly increases by 4 months (≈8.0% aortic, ≈6.7% mitral) and 16 months (≈10.9% aortic, ≈10.5% mitral) of age (Figure A).…”
Section: Resultsmentioning
confidence: 73%
“…Here, we used C57 / Bl6 WT mice to show that CD45‐positive cells are detected in endocardial cushions of primitive aortic valves at embryonic day 14.5, and reactivity is also observed in the mitral position, but the percentage of cells is significantly lower (Figure A). It is not known whether these cells are embryonic hematopoietic stem cells derived from primitive or definitive hematopoiesis, or tissue‐resident hematopoietic cells . Similar percentages of CD45‐positive cells are observed at postnatal stages in both valve sets (≈1.2% aortic, ≈2.6% mitral), but the percent significantly increases by 4 months (≈8.0% aortic, ≈6.7% mitral) and 16 months (≈10.9% aortic, ≈10.5% mitral) of age (Figure A).…”
Section: Resultsmentioning
confidence: 73%
“…TET2 and TET3 were such as to participate in demethylation of liver development in the late Kunming mouse fetus. TET‐mediated oxidation of 5mC to 5hmC, 5fC, or 5caC is considered to be the main force for fetal liver differentiation (Lewis et al, ; McGrath et al, ). In the late stage of Kunming fetus, the expression of 5hmC was significantly associated with the formation of liver tissue and TET2 was strongly positive, which suggested that TET2 is related to the development of hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that some tissue-resident macrophage populations (such as microglia in the brain) arise in the yolk sac during early embryogenesis and populate the tissues of the developing embryo, where they can be maintained by self-renewal for long periods (even throughout life) (Hashimoto et al, 2013; Schulz et al, 2012). Other tissue-resident macrophage populations arise from circulating monocytes produced by hematopoietic stem cells (HSCs), initially in the fetal liver and subsequently in the bone marrow (Geissmann and Mass, 2015; McGrath et al, 2015). Neutrophils and DCs are also derived from HSCs.…”
Section: Introductionmentioning
confidence: 99%